2009
DOI: 10.2337/dc09-1220
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in an Estimated Measure of Insulin Resistance Among Individuals With Type 1 Diabetes

Abstract: OBJECTIVEInsulin resistance is greater in racial/ethnic minorities than in non-Hispanic whites (NHWs) for those with and without type 2 diabetes. Because previous research on insulin resistance in type 1 diabetes was limited to NHWs, racial/ethnic variation in an estimated measure of insulin resistance in type 1 diabetes was determined.RESEARCH DESIGN AND METHODSThe sample included 79 individuals with type 1 diabetes diagnosed at age <18 years (32.9% NHWs, 46.8% non-Hispanic black [NHB], 7.6% other/mixed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
4
39
1
1
Order By: Relevance
“…This is consistent with a multiethnic study of 1,086 nondiabetic individuals; Haffner et al (6) showed that African Americans and Hispanics were more IR (using the frequently sampled intravenous glucose tolerance test) than non-Hispanic whites. Danielson et al (16) examined insulin sensitivity using eGDR in a pediatric multiethnic cohort with type 1 diabetes ( n = 79) and found less IR among non-Hispanic whites compared with other ethnic groups; in contrast to our study, the average age of patients in the study by Danielson et al was 13.5 years, ranging from 3.2–32.5 years, and all patients had onset of type 1 diabetes before age 18.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with a multiethnic study of 1,086 nondiabetic individuals; Haffner et al (6) showed that African Americans and Hispanics were more IR (using the frequently sampled intravenous glucose tolerance test) than non-Hispanic whites. Danielson et al (16) examined insulin sensitivity using eGDR in a pediatric multiethnic cohort with type 1 diabetes ( n = 79) and found less IR among non-Hispanic whites compared with other ethnic groups; in contrast to our study, the average age of patients in the study by Danielson et al was 13.5 years, ranging from 3.2–32.5 years, and all patients had onset of type 1 diabetes before age 18.…”
Section: Discussioncontrasting
confidence: 87%
“…Furthermore, we confirmed that low eGDR is associated with an increased risk of diabetes vascular complications. Although the concept of IR among individuals with type 1 diabetes is not new (35), few studies have explored this phenomenon in nonwhite populations or assessed interethnic differences (6,16). To our knowledge, this is the first study of adults with type 1 diabetes that was adequately powered to analyze eGDR, demographic and metabolic confounders, and diabetes complications among three major ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 In addition, differences in insulin resistance (IR) are another possible factor. Danielson et al 39 showed that IR was significantly lower in NHW youth than in minority youth with T1DM.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…The progression of NAFLD in the setting of insulin resistance is likely to be driven by the pathogenic effects of the subsequent hyperinsulinemia and also by varying degrees of relative insulin deficiency, particularly in diabetes. Insulin resistance is almost invariable in type 2 diabetes, and it is also increasingly recognized as an ongoing issue in many patients with type 1 diabetes, especially those of increasing age (175,176). By definition, prediabetes and diabetes are states of relative insulin deficiency that, when combined with excess caloric intake and obesity, will commonly contribute to increased portal fatty acids and ectopic fat deposition, including in the liver.…”
Section: A Seeming Paradox: Insulin Resistance With Hyperinsulinemia mentioning
confidence: 99%